TIPOLOGI ÛLÛ AL-BÂB: ANALISIS SEMANTIK AYAT-AYAT ALQURAN DAN IMPLEMENTASINYA DALAM PENDIDIKAN ISLAM - Muhammad Nur Asmawi (State Institute of Islamic Studies (IAIN) Palu, 2008)
This paper deals with the concept of ûlû al-bâb in the Qur’an. While studying the concept, thematic approach (tafsîr maudû‘î) and semantical analysis will be employed. The steps include collecting sixteen Quranic verses related to ûlû al-bâb, classifying them according to typologies, and analyzing them. With these steps, a whole framework of this concept will be revealed, as well as the constructs of the term ûlû al-bâb. Based on the grammatical analysis, the meaning of ûlû al-bâb is constructed according to its position as munâda, fâ‘il, sifah and khabr. Based on this analysis, ûlû al-bâb covers such meanings as al-râsikhûn fī al-‘lm, qawm yatafakkarûn, ahl al-dhikr and ashâb al-‘uqûl. These meanings show educational activities which include principles and purposes, that is, to create knowledgeable-pious human beings, who are useful for humanity.Kata Kunci: tipologi ûlû al-bâb, al-dhikr, ayat Alquran, analisis semantik, pendidikan Islam